Former male elite athletes have better metabolic health in late life than their controls - Laine, M. K.; Eriksson, J. G.; Kujala, U. M.; Kaprio, J.; Loo, B.-M.; Sundvall, J.; Bäckmand, H. M.; Peltonen, M.; Jula, A.; Sarna, S. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Elite-class athletes have longer life expectancy and lower risk for chronic noncommunicable diseases possibly because of physically active and healthier lifestyle. In this study, we assessed former male Finnish elite-class athletes` (n = 392) and their matched controls` (n = 207) body composition, and risk for the metabolic syndrome (MS) and nonalcoholic fatty liver disease (NAFLD) in later life. Compared with the controls, the former athletes had lower body fat percentage (24.8% vs 26.0%, P = 0.021), lower risk for MS [odds ratio (OR) 0.57, 95% confidence interval (CI) 0.40-0.81], and NAFLD (OR 0.61, 95% CI 0.42-0.88). High volume of current leisure-time physical activity (LTPA) was associated with lower body fat percentage (P for trend?<?0.001). When current volume of LTPA increased 1 MET h/week, the risk of MS and NAFLD decreased (OR 0.99, 95% CI 0.98-0.99 and OR 0.97, 95% CI 0.96-0.98, respectively). Although a career as an elite-class athlete during young adulthood may help to protect from developing metabolic syndrome, present exercise levels and volume of LTPA seem equally important as well